Pengaruh Profesionalisme, Komitmen Organisasi, Gaya Kepemimpinan, dan Budaya Organisasi Terhadap Kinerja Auditor Pada Kantor Akuntan Publik Di Pekanbaru - Dariana Dariana; Ria Refina (Politeknik Negeri Bengkalis, 2020)
This study was conducted to determine the effect of professionalism, organizational commitment, leadership style and organizational culture on auditor performance. This research was conducted at the Public Accounting Firm in Pekanbaru. This data collection was carried out by giving a questionnaire of 30 copies, which were distributed to respondents who were senior auditor staff and junior auditor staff. The data obtained were then analyzed using SPSS version 22.0. the results of this test indicate that professionalism, organizational commitment, leadership style and organizational culture have a positive and significant effect on auditor performance. The contribution of the influence of the independent variable to the dependent variable was 89.8% while the remaining 10.2% was influenced by other variables.Keywords: Professionalism, Organizational Commitment, Leadership Style, Organizational Culture, Auditor Performance